An activated‐zinc oral rinse reduces pro‐inflammatory cytokine secretion and promotes proliferation in Porphyromonas gingivalis LPS‐challenged gingival tissues – A pilot study. Issue 6 (6th May 2021) - Stanton, Kaitlyn A.; McCracken, Barbara A.
Abstract: Objectives: The use of adjunct post‐treatment mouth rinses containing chlorhexidine (CHX) for periodontitis patients is associated with side effects that reduce patient compliance. Our aim was to evaluate the proinflammatory and cell proliferation effects of an activated‐zinc mouth rinse (SM) that has been suggested as an alternative post‐treatment therapeutic. Materials and Methods: Tissue models of gingival epithelium were used to simulate periodontal disease and compare inflammatory reactions after treatment with CHX or SM. Tissues were exposed to Porphyromonas gingivalis LPS and wounded to simulate periodontal disease. Tissues were treated and incubated for 6, 12, or 24 h. Inflammatory cytokines were measured in culture medium by ELISA and local expression of Toll‐like receptor (TLR)‐4 and proliferation marker Ki‐67 was visualized by immunohistochemistry. Results: SM and CHX treatments decreased secretion of IL‐1β and IL‐8 into culture media at all time points. IL‐1β secretion levels were further decreased by SM compared to CHX treatment at all time points. TLR‐4 expression appeared significantly increased 12 h post‐treatment in the CHX tissues but remained relatively low in SM tissues at all time points. Ki‐67 results suggest that cell proliferation was increased in the SM tissues earlier than CHX tissues. Conclusions: Our data suggest that SM may reduce inflammation in gingival tissues.